Fabrication of a kinetically sprayed CuO ultra-thin film to evaluate CO gas sensing parameters. (8th May 2019) - Choi, Dahyun; Kim, Hyojun; Son, Minhee; Kim, Hyungsub; Lee, Hee Chul; Lee, Caroline Sunyong
Abstract : We have introduced a new fabrication process for a CO gas sensor using a kinetically sprayed Cu thin layer, followed by oxidation at 250 °C. Abstract : We have introduced a new fabrication process for a CO gas sensor using a kinetically sprayed Cu thin layer, followed by oxidation at 250 °C. The resulting 200 nm-thick CuO thin layer exhibited semi-transparent optical properties. The as-fabricated CO gas sensor was tested under two conditions with varying CO gas concentration ranging from 1000 to 5000 ppm and operating temperatures of 200, 250, and 300 °C: (1) a reaction time of 600 s and a recovery reaction time in an air atmosphere of 1800 s; and (2) a gas reaction time of 1200 s and a recovery time of 7200 s. As a result, the sensor response showed its improvement under a high operating temperature of 300 °C with a reaction time of 600 s and a recovery time of 1800 s regardless of the CO gas concentration. In contrast, the response of the CuO gas sensor showed its maximum value of 0.209 at a lower temperature of 200 °C, due to a sufficient recovery time of 7200 s. Therefore, we have proved that a kinetically sprayed CuO thin layer can be operated with varying CO gas concentration, as well as varying the temperature and time, to be useful as a gas sensor.